Selective Swelling and Functionalization of Integral Asymmetric Isoporous Block Copolymer Membranes. Issue 16 (31st May 2021) - Rahman, Md. Mushfequr
Abstract: SNIPS stands for a membrane fabrication technique that combines the evaporation induced self‐assembly of the block copolymers and the classical nonsolvent induced phase separation. It is a one‐step readily scalable technique to fabricate integral asymmetric isoporous membranes. The prominent developments in the last decade have carved out a niche for SNIPS as a potential technique to fabricate next generation isoporous membranes. In the last decade, a rich polymer library and variety of membrane postmodification routes have been successfully implemented to fabricate SNIPS membranes having the desired pore functionality. Some of these membranes form soft nanochannels in hydrated state due to swelling of the pore wall, i.e., the pore forming block of the block copolymer. These membranes having soft nanochannels have demonstrated the potential to perform several challenging separation tasks in ultrafiltration and nanofiltration. This paper highlights the currently accessible pore functionality, the strategies to tune the swelling of the soft nanochannels, the potential applications, and future perspectives of these membranes. Abstract : The integral asymmetric isoporous block copolymer membranes prepared by SNIPS contain an isoporous layer on top of a highly porous spongy substructure. Selective swelling of the pore forming block of the block copolymer in a hydrated state is an effective tool to tune the effective pore size of the isoporous layer.